Parkinson’s Disease and Cognitive Impairment - Yang Yang; Bei-sha Tang; Ji-feng Guo (Parkinson's Disease)
Parkinson’s disease (PD) is a progressive neurodegenerative disease primarily characterized by the hallmarks of motor symptoms, such as tremor, bradykinesia, rigidity, and postural instability. However, through clinical investigations in patients and experimental findings in animal models of Parkinson’s disease for years, it is now well recognized that Parkinson’s disease is more than just a motor-deficit disorder. The majority of Parkinson’s disease patients suffer from nonmotor disabilities, for instance, cognitive impairment, autonomic dysfunction, sensory dysfunction, and sleep disorder. So far, anti-PD prescriptions and surgical treatments have been mainly focusing on motor dysfunctions, leaving cognitive impairment a marginal clinical field. Within the nonmotor symptoms, cognitive impairment is one of the most common and significant aspects of Parkinson’s disease, and cognitive deficits such as dysexecutive syndrome and visuospatial disturbances could seriously affect the quality of life, reduce life expectancy, prolong the duration of hospitalization, and therefore increase burdens of caregiver and medical costs. In this review, we have done a retrospective study of the recent related researches on epidemiology, clinical manifestation and diagnosis, genetics, and potential treatment of cognitive deficits in Parkinson’s disease, aiming to provide a summary of cognitive impairment in Parkinson’s disease and make it easy for clinicians to tackle this challenging issue in their future practice.